MISSILES AND AIRCRAFT (PART 3) - Meyer, C. (Scientia Militaria - South African Journal of Military Studies, 2012)
The initial stages of the war Every national force in Europe is weaker than we are. We can conquer in one week the area from Khartoum to Baghdad and Algeria. Major General Ariel Sharon’